Strategi Pemasaran Kombucha Cascara Menggunakan Konsep Marketing Mix 7P dengan Analisis Matriks SWOT dan QSPM (Studi Kasus PT Agritama Sinergi inovasi Kota Bandung) - Tazkia Khaerunnisa; Iwan Setiawan; Lucyana Trimo; Gema Wibawa Mukti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
The increasing trend of a healthy lifestyle parallels the growing awareness among the Indonesian public of consuming healthy beverages, including the fermented drink kombucha. PT Agritama Sinergi Inovasi, as a start-up company that will market its newly developed product, kombucha cascara, will undoubtedly face new challenges considering the competitive landscape of the herbal beverage industry. This study aims to analyze PT Agritama Sinergi Inovasi Kombucha cascara's internal and external marketing factors and formulate priority marketing strategies for the product. This research employs a qualitative method with a case study approach. The data used include both primary and secondary data. Primary data were directly obtained from informants involved in the marketing of kombucha cascara at PT Agritama Sinergi Inovasi through in-depth interviews, guidance interviews, and direct field observations. Secondary data were sourced from various literature studies related to this research. The marketing strategy formulation was conducted using the 7P marketing mix concept. The data analysis of this research utilized the IFE and EFE matrices, the IE matrix, and processing into the SWOT matrix to derive alternative strategies and the QSPM matrix to determine the best strategy to prioritize within the company. The research results indicate that the marketing conditions of kombucha cascara at PT Agritama Sinergi Inovasi have an excellent internal and external position, as it scores above 2.50, meaning that the marketing of kombucha cascara has been able to leverage its strengths and address its weaknesses, as well as effectively exploit opportunities to overcome threats. The marketing of kombucha cascara at PT Agritama Sinergi Inovasi is in the grow and build stage, so the appropriate implementation strategies are intensive and integrative. Ten alternative strategies were identified, with the priority strategy for marketing PT Agritama Sinergi Inovasi Kombucha cascara being the expansion of distribution channels and geographical expansion.